Successful Laparoscopic Management of Primary Abdominal Pregnancy in the Cul-De-Sac - Richard Shih-Hung Young; Ming-Chao Huang; Chih-Ping Chen (Elsevier, 2005)
Objective: We report a rare case of primary abdominal pregnancy in the Douglas cul-de-sac that was successfully treated with laparoscopy. Case Report: A 31-year-old primigravida woman had undergone intrauterine insemination 5 weeks prior to presentation. Ultrasound examination at presentation revealed an ectopic gestational sac in the cul-de-sac without any evidence of intrauterine pregnancy, and serum β-human chorionic gonadotropin (β-hCG) was 46,601 mIU/mL. Laparoscopy was performed and revealed an ectopic mass implanted in the cul-de-sac. The gestational tissue was removed by grasping forceps and hydrodissection. Bipolar electrocauterization and tamponading with Surgicel(tm) were used for hemostasis at the defect of the peritoneum. Serum β-hCG fell rapidly after surgery. The patient had a term baby delivered successfully 2 years postoperatively. Conclusion: Early diagnosis of abdominal pregnancy enabled successful laparoscopic management.